Decreased Medial Prefrontal Cortex Glutamate Levels in Perimenopausal Women - Yap, Sidney; Luki, Jessica; Hanstock, Christopher C.; Seres, Peter; Shandro, Tami; Hanstock, Sarah E. C.; Lirette, Alynna; Zhao, Huaying (Helen); Aitchison, Katherine J.; Le Melledo, Jean-Michel (Frontiers in Psychiatry, 2021)
Objective: There is an increased risk of experiencing depression during perimenopause, a period of rapidly changing female hormone concentrations. Women at particular risk of developing major depression during perimenopause are those with history of mood sensitivity to female hormone fluctuations i.e., women with a history of premenstrual dysphoric disorder and/or post-partum depression. Depressive symptomology has been associated with fluctuations of glutamate levels in the medial prefrontal cortex in major depression patients as well as premenstrual dysphoric disorder and post-partum depression patients. The objective of the study was to compare medial prefrontal cortex glutamate levels in healthy perimenopausal and reproductive-aged women. Methods: Medial prefrontal cortex glutamate levels in healthy perimenopausal (n=15) and healthy reproductive-aged women (n=16) were compared via Magnetic Resonance Spectroscopy scan using a 3 Tesla magnet. Absence of depressive symptomology and psychiatric comorbidity was confirmed via semi-structured interview. Participants were scanned during the early follicular phase of the menstrual cycle. Results: Mean medial prefrontal cortex glutamate concentrations were decreased in the perimenopause group compared to reproductive-aged group (perimenopause mean=0.57±0.03, reproductive-aged mean=0.63±0.06, t=-3.84, df=23.97, p=0.001). Conclusion: Perimenopause is associated with decreases in medial prefrontal cortex glutamate levels. This decrease may be contributing to the increased risk of experiencing depression during perimenopause. Further research should assess medial prefrontal cortex glutamate levels in perimenopausal women suffering from major depression.